Islamophobia in Multicultural America: Media Narratives, Challenges, and Muslim Responses - Noviati, Cora Elly; Permata, Octora; Hakim, Encik Lukmanul; Iriyanto, Gatot (Kawanua International Journal of Multicultural Studies, 2024)
This research examines the phenomenon of Islamophobia in the context of American multiculturalism, focusing on the interactions between media narratives, civil rights challenges, and Muslim community responses. Employing qualitative methods and literature review, this study analyzes the representation of Islam in media, the impact of policies on Muslim rights, and strategies developed by Muslim organizations to counter discrimination. The findings indicate that media plays a significant role in shaping public perception, often reinforcing negative stereotypes. However, Muslim communities have developed innovative approaches to counter these narratives, including the use of digital media and cross-sectoral collaboration. Civil rights challenges reflect the tension between national security and religious freedom, although there are positive trends in the development of more inclusive legislation in some states. Intercultural dialogue efforts demonstrate potential for reducing prejudice, yet still face challenges in expanding their impact. This research concludes that a multifaceted approach is necessary to address Islamophobia and promote an inclusive multicultural society, involving media reform, policy advocacy, public education, and strengthening intercultural dialogue.